Kajian Literatur Tentang Tantangan Profesionalisme Guru Bimbingan dan Konseling di Madrasah Aliyah Negeri - Nur Hisna Daniati; Rosalinda Rosalinda; Neviyarni S; Yarmis Syukur (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This research examines the challenges of professionalism of Guidance and Counseling (BK) teachers in Madrasah Aliyah Negeri (MAN) through literature review. BK services have an important role in supporting students' academic and psychosocial development, but face obstacles such as the limited number of professional BK teachers and educational backgrounds that are not in accordance with the BK field. The non-ideal ratio of teachers to students and high workload also hamper the effectiveness of services. In addition, the management of services that are not yet based on student needs and the lack of continuous training are significant challenges. This study used a literature review method with descriptive analysis to identify these factors. The results suggest improving the quality of human resources through professional training, strengthening service management, and policy support from madrasahs and the government. The professionalism of counseling teachers has a direct impact on the quality of services that affect students' academic achievement and psychosocial well-being. The main recommendation is to increase the recruitment of qualified counseling teachers and continuous competency development to support effective and relevant counseling services in MAN.